Paremiological system of Belarusian and Russian languages: differences vs. similarities (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
We have suggested new method of typological comparison of paremiological systems in (closely)related languages. Similarities and differences in structure and semantics of aphorisms in Russian and Belarusian languages were determined and systematized, specific structural and semantic peculiarities in aphoristic paremias of these languages were described. The importance of interlanguage similarities and differences, nearness vs. remoteness of the Belarusian and Russian languages on the aphoristic (paremiological) level was determined on the basis of quantitative analysis of structural and semantic similarities and differences of the aphoristic paremias in Russian and Belarusian languages. It was proved, that specifics of structure and semantics of aphoristic paremiology in (closely) cognate languages are determined by their national and cultural peculiarities (in ways and selectiveness of revealing the «world» in aphoristic paremias) and do not depend on the degree of relationship.
Keywords: typology of languages; Belarusian language; Russian language; paremiological system of language; interlanguage distinctions of aphorisms-paremias in lexical and grammatical structure and semantics